PENGARUH PROFITABILITAS, KEBIJAKAN UTANG DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2021–2 - Novia Rahwatul Husnah; Ronni Andri Wijaya; Silvia Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the effect of profitability, debt policy, and dividend policy on firm value with firm size as a moderating variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021–2025. Secondary data from annual financial reports were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with a sample of 25 companies (125 observations) selected through purposive sampling. The results show that profitability has a positive and significant effect on firm value, debt policy has no significant effect, while dividend policy has a negative and significant effect. Firm size does not moderate the effect of profitability, but it weakens the negative effect of debt policy and strengthens the negative effect of dividend policy. Simultaneously, the independent variables contribute 30.3% to firm value before moderation, increasing to 66.6% after firm size and the interaction terms are included in the model.